Can open government support innovation for inclusive development? A South African case study. (12th July 2021) - Plantinga, Paul; Adams, Rachel
The opening of government in a number of countries has implications for innovation processes and the potential for inclusive development outcomes. After unpacking key thinking around openness and its attendant values, we explore the adoption of open government practices in innovation by considering four instruments: the opening of innovation and technology policy processes, co-creation and collaborative solution development by civil servants, government entities acting as innovation brokers, and public sector procurement of innovation. Through a case study of South Africa, we highlight how innovation actors prioritise particular values of openness over others, oftentimes at the expense of legality and impartiality. This oversight leads to project failures, legitimacy crises and exploitation of openness by more powerful entities. In response, we suggest that public sector innovation programs and platforms can more explicitly recognise and balance different values through appropriate institutional forms and legislation, and thereby enable sustainable application of open government practices.